(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This research explores both causal and correlational links between the quality of corporate governance and the level of investor confidence. Using an evidence-driven analytical framework, the study suggests that well-structured corporate governance systems play a significant role in strengthening investor confidence by minimizing information asymmetry, reducing perceived investment risk, and enhancing the efficiency of managerial decision-making. Findings from global financial markets indicate that companies with stronger governance practices generally experience higher market valuation, lower financing costs, and greater participation from institutional investors. Overall, the results support the view that corporate governance serves as a key factor influencing investment efficiency and the overall stability of financial markets.